2018
DOI: 10.1111/apa.14602
|View full text |Cite
|
Sign up to set email alerts
|

Snus users had high levels of nicotine, cotinine and 3‐hydroxycotinine in their breastmilk, and the clearance was slower than in smoking mothers

Abstract: Aim Using snus, an oral moist tobacco, has increased among pregnant women in Sweden, the only European Union country where sales are legal. This study evaluated whether snus generated similar concentrations of nicotine and its metabolites in breastmilk to cigarette smoking. Methods We analysed 49 breastmilk samples from 33 nursing mother – 13 snus users, six cigarette smokers and 14 controls – for concentrations of nicotine, cotinine and 3‐hydroxycotinine. The mothers were recruited at antenatal clinics in Swe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Nordenstam et al. report that snus users in their study had high levels of nicotine and metabolites in their breastmilk and nicotine was even found after 12.5 hours of abstinence. Readers may also be interested in the mini‐review by Kreyberg et al.…”
Section: Nicotine Use During Pregnancy and Breastfeedingmentioning
confidence: 85%
“…Nordenstam et al. report that snus users in their study had high levels of nicotine and metabolites in their breastmilk and nicotine was even found after 12.5 hours of abstinence. Readers may also be interested in the mini‐review by Kreyberg et al.…”
Section: Nicotine Use During Pregnancy and Breastfeedingmentioning
confidence: 85%
“…We found no study assessing potential effects on the infant by snus and NRT exposure through breast milk. A recent study reported however that snus users had higher levels of nicotine in their breast milk compared with smokers . Breastfeeding is important for infant health, yet potential risk of exposure to nicotine from breast milk remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine easily passes the placenta and can be detected in human foetal circulation and amniotic fluid at concentrations higher than those in the maternal plasma . Further, compared with smoking, snus used by breastfeeding women has been shown to give higher levels and prolonged presence of nicotine in breast milk, with at least 12.5 hours in snus users and four hours in smokers following abstinence .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Moreover, breastfed infants exposed to smoking or snus by their nursing mothers are exposed to high levels of nicotine through the breast milk. 4,5 Nicotine may remain in the breast milk for 12.5 hours after the last snus dose and 4 hours after the last cigarette. 5 Smoking during breastfeeding has been shown to reduce the health promoting properties of breast milk including lower fat concentration, reduced milk production possibly through reduced levels of prolactin, shorter breastfeeding periods 6 and may affect the taste of the breast milk.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Nicotine may remain in the breast milk for 12.5 hours after the last snus dose and 4 hours after the last cigarette. 5 Smoking during breastfeeding has been shown to reduce the health promoting properties of breast milk including lower fat concentration, reduced milk production possibly through reduced levels of prolactin, shorter breastfeeding periods 6 and may affect the taste of the breast milk. Moreover, an increased risk for several conditions has been observed in the smoke-exposed infant, including colic, sleep disruption, 7 allergies, respiratory disorders, 6,8 neurobehavioural disorders, 7 sudden infant death syndrome, 6,7 altered heart rate variability, 9 and overweight and obesity later in life.…”
Section: Introductionmentioning
confidence: 99%